Computational fluid dynamics : an introduction to modeling and applications - Khalil, Imane; Lakkis, Issam (New York : McGraw Hill, 2023)
'This book is not a traditional computational fluid dynamics (CFD) textbook. While current CFD books explain and derive the numerical methods used to solve fluid dynamics problems, programming these methods on computers is a tedious process for undergraduate engineering students who are primarily interested in using com-putational modeling software to solve engineering problems without're-inventing the wheel''--
Includes bibliographical references (page 285-286) and index.
Keywords: Fluid mechanics